Investigating the role of a pyrabactin resistance 1-like abscisic acid receptor gene to improve drought tolerance in sugarcane - Fischer, Riette Louwrene (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.